2020
DOI: 10.13106/jafeb.2020.vol7.no11.737
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous Innovation in Mediating Entrepreneurial Creativity on Firm Performance and Competitive Advantage

Abstract: A new business venture faces intense competition in a dynamic environment. To survive, new business ventures and established companies both need to generate creativity and significant new ventures to be highly competitive and have high levels of performance. In this study, we examined new business ventures that determined their competitiveness and performance generated from entrepreneurial creativity and mediated by ambidextrous innovation. This research used survey data collected from 143 Indonesian's new bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Empirical studies have shown that EI plays a vital role in improving organizational performance (Kajalo and Lindblom, 2015;Sumiati, 2020a, b). Therefore, based on the previous literature, we conclude a significant relationship between KMC and organizational performance through EC, organizational ambidexterity and EI (Sijabat et al, 2020;Tseng and Lee, 2014).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Empirical studies have shown that EI plays a vital role in improving organizational performance (Kajalo and Lindblom, 2015;Sumiati, 2020a, b). Therefore, based on the previous literature, we conclude a significant relationship between KMC and organizational performance through EC, organizational ambidexterity and EI (Sijabat et al, 2020;Tseng and Lee, 2014).…”
Section: Introductionmentioning
confidence: 54%
“…Given the relationship between creativity and innovation, some researchers have acknowledged that creativity is used to enhance innovation ambidexterity (Lestari et al, 2020;Subramaniam and Youndt, 2005). EC has a significant impact on the growth of innovative activities in any enterprise (Baron and Tang, 2011), affects both process innovation and product innovation, and plays a significant role in promoting ambidexterity by balancing exploratory and exploitative innovations (Sijabat et al, 2020). EC facilitates communication, and EC outcomes can increase innovation ambidexterity (Somech and Drach-Zahavy, 2013).…”
Section: Entrepreneurial Creativity and Ambidexteritymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ambidextrous learning for competitive advantage has been confirmed by many researchers (Sijabat et al, 2020;Wang and Fang, 2021). In related studies, exploratory learning and exploitative learning are always used to explain the mechanism of the effects of certain organizational capabilities on sustainable competitive advantage (Yang and Wang, 2020;Yang et al, 2021).…”
Section: Ambidextrous Learningmentioning
confidence: 90%
“…Moreover, the sufficient number and type of knowledge resources are important inducements for the organization to form irreplaceable resources and capabilities, which help the firm to continuously improve its competitive ability ( Yang et al, 2021 ). Exploratory learning affects enterprises’ ability to adapt to the new environment and decision-making speed and emphasizes experiment and innovation ( Li et al, 2013 ; Sijabat et al, 2020 ; Zhou et al, 2021 ). It breaks existing learning paths and practices, promotes the reorganization and reconstruction of resources, and improves organizational environment adaptability.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%